Universal High-Speed Broadband Provision: An Alternative Policy Approach - Elmar G. Wolfstetter (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Millions of citizens and firms lack access to high speed internet, even though governments pledged to spend huge sums of money to subsidize internet networks. In this paper we review some systematic flaws of present subsidy policies and outline a promising alternative. We propose that governments should treat the broadband infrastructure as a public responsibility and set up intelligently designed public-private partnerships that fund and temporarily operate the broadband in exchange for collecting service fees and, if necessary, subsidies. Simple “least-present value of revenue” auctions should be used to award all concessions, not only those that require subsidies, and concessions should flexibly revert to public ownership depending on realized revenues. This procurement method is easy to use, immune to strategic manipulations and renegotiations, and has already proven successful in procuring toll-roads and bridges.
Keywords: D44; D47; D86; H20; H54; L96; 330; public-private partnerships; auctions; universal service auctions; high-speed broadband provision; public finance